PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL KOOPERATIF TIPE STAD DI KELAS V SEKOLAH DASAR - Fatimah, Siti; Bistari, Bistari; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to describe the improvement of students ability of mathematic lessonby using cooperative learning type STAD on the fifth grade students at SDN 21 Pontianak Timur.The method used in this research is descriptive method, kind of this research is classroom action research and the nature of the research is collaborative. The research subject included teacher and 28 students of VB class. The data collecting technique were direct observation and measurement. The tols used were observation sheets and test. The findins of the research show an increase in the average score for teacher’s ability to compose lesson plans from 3,19 in cycle I to be 3,72 in cycle II. The ability of teachers to implement cooperative learning type STAD with an average score from 3,33 in cycle 1 to 3,78 in cycle II. Moreover, the average score of students’ learning outcomes had an improvement from 65,62 in cycle I to 83,57 in cycle II. The findings indicated that the teacher’s ability to compose lesson plans and to conduct teaching, as well as the student’s learning outcomes of mathematics by using cooperative learning type STAD in the fifth grade students SDN 21 Pontianak Timur could be improved. Keywords: Cooperative Learning Type STAD, Learning Outcomes, Mathematic